Technological Development in Wholegrain Food Processing - Francesca Nocente; Laura Gazza (Foods)
This review aims to give evidence of the current developments and potential applications of emerging technological methods to improve the technological performance and the sensorial acceptability of wholegrain products. The review explores the technologies based on physical, i.e., micronization, steam explosion, high hydrostatic pressure, extrusion cooking, ohmic heating, and 3D printing, and biotechnological methods, such as fermentation and enzymatic treatments in the pre-milling, milling, and transformation steps of wholegrain products. The literature from the past decade for this review article was collected from electronic databases such as ScienceDirect, PubMed, Google Scholar, and Web of Science.